Who Said That? Citing Sources in Social Science Research - Emily Rhoades; Brian E. Myers (EDIS)
AEC-380, a 5-page fact sheet by Emily Rhoades and Brian E. Myers, provides justification and basic guidelines for following APA style, and provides standard citation formats with examples for citations in text and in references or works cited pages.  Published by the UF Department of Agricultural Education and Communication, November 2006.